Development and Characterization of Niosomal gel of Acelofenac for the treatment of Arthritis - Shipra , Dr Reenu Yadav, Phool singh yaduvanshi, Gaurav Jain, Dr Sonu Sharma (Drugs and Cell Therapies in Hematology, 2021)
In the symptomatic treatment of rheumatoid arthritis, osteoarthritis, and ankylosing spondylitis, aceclofenac is regarded the first-line medication. The successful treatment of arthritis relies on the body’s ability to maintain an effective drug concentration level, which necessitates a steady and consistent delivery of the drug. Aceclofenac is an attractive candidate for sustained release because of its short biological half-life (approximately 4 hours) and frequent dosing (more than thrice a day), as well as the fact that 2/3 of the dose (70-80%) is eliminated by renal transport. To forecast the release mechanism and compare release profiles, mathematical models are widely used. The best fitting linear parameter for formulations F1 and F2 was determined to be zero order models, with correlation coefficients of 0.996 and 0.985, respectively. These findings imply that niosome-containing gels are a suitable formulation for aceclofenac local delivery.